Ineffectual Medical Treatment of Cesarean Scar Ectopic Pregnancy With Systemic Methotrexate - Sefa Kelekçi; Serpil Aydoğmuş; Hüseyin Aydoğmuş; Serenat Eriş; Emine Demirel; Halime Şen Selim (SAGE Publishing, 2014)
The implantation of a pregnancy within the scar of a previous cesarean section is known as a "cesarean scar pregnancy." Its incidence was reported to be 6.1%. However, with the increasing rates of cesarean sections, the incidence is expected to rise. A variety of conservative and surgical treatment modalities have been proposed for the management of cesarean scar pregnancy; however, there are no optimal universal treatment guidelines because of its rarity. Treatment should be tailored to the individual patient. It is obvious that more scar pregnancies will be seen in the future and therefore a set of criteria for the choice of various modes of management should be developed. Here, we present 2 cases of cesarean scar pregnancies treated with a local injection of potassium chloride after the failure of methotrexate administration.